Business Plan Nutrizerts - Cantara, Mary Rose A.; Carbonell, Regine Christianne Myrhh U.; Dela Cruz, Shaula Lyn; De Leon, Marinette B.; Diputado, Jean Paula D.; Insigne, May Ferlyn H.; Magpayo, Annaleen M.; Odonio, Michelle L.; and Querubin, Josephine R. 4 0 16; 5
u
Business Plan: (Bachelor of Science in Entrepreneurship)- Pamantasan ng Lungsod ng Maynila, 2012.
Keywords: 2 -- 0; 6; 20; 20; 2